Скорость распространения процесса в очаге как базовый параметр квазидинамических моделей: особенности алгоритма определения, по данным группы станций - Костинский, А.С. (Видавничий дім "Академперіодика" НАН України, 2008)
Attention is called to the process propagation velocity preferred position in the collection of parameters of focal models and the quantitative assessment significance of a reduced value ζ = v/c even for models with constant velocity v = const (c is the elastic wave velocity). The scheme of determination of the ratio ζ by records of three stations logically completes the author’s computational algorithm based on the time integration of a displacement with weight factors f(t) = tn, n = 0, 1, 2, . . ..